Post a New Question


posted by .

solve using substitution
4x + 3y= -3
2x + y = -1

  • math -

    When we look at the second equation, we can transfer the term 2x to the other side of the equality. We get that:

    2x+y = -1
    <=> y = -1-2x

    when we replace the y in the first equation by the value we just calculated, we get that:

    4x + 3y= -3
    <=> 4x + 3(-1-2x)=-3
    <=> 4x - 3 -6x = -3
    <=> -2x=0
    <=> x=0

    So, we find that x=0. When we replace this value for x in the equation we earlier found for y, we get that:


    So, we find that x=0 and y=-1

  • math -


Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question